Hydraulic Analysis of Flood Characteristics in Way Sekampung Watershed Using HEC-RAS with Various Return Periods - Finanda, Reysa; Arifaini , Nur; Zakaria, Ahmad; Wahono, Endro (Jurnal Teknik Sipil dan Lingkungan, 2025)
A river is a flow of water that flows in one direction from a high area to a low area by gravity or from upstream to downstream. Although there have been many studies using HEC-RAS software, its application in Way Sekampung watershed still needs further evaluation. The purpose of this study is to analyze the high elevation of overflow that occurs at the reviewed location and analyze the comparison between permanent and non-permanent flows of flood tide elevation in Way Sekampung watershed. The flood discharge values for the 10, 25, 50, and 100-year re-periods were 506.01 m3/s, 576.82 m3/s, 627.01 m3/s, and 675.20 m3/s, respectively. Meanwhile, in the hydraulic analysis, the high elevation of the flood water level of the unsteady flow was obtained from the results of the hydraulic analysis using the HEC-RAS V6.5 application at 10, 25, 50 and 100 years repeatedly, namely 177.57 meters, 179.63 meters, 183.86 meters, and 192.73 meters in the upstream part. In addition, in the downstream part, 95.49 meters, 97.53 meters, 101.28 meters, 106.52 meters were obtained for each re-period. and experienced overflow heights of 5.57 m, 6.54 m, 6.99 m, and 16.03 m during the 10-year, 25-year, 50-year, and 100-year periods. From the results of the research that has been carried out, it is concluded that in the upstream and downstream areas there will be no flooding because the flood water level is still lower than the high elevation of the left and right river banks.